Bacterial quorum sensing molecule induces chemotaxis of human neutrophils via induction of p38 and leukocyte specific protein 1 (LSP1) - Kahle, Nadine; Hänsch, Gertrud Maria (Immunobiology, 2013)
When bacteria colonize surfaces, they socialize and form biofilms. This process is well regulated and relies on the communication among the bacteria via so-called “quorum sensing molecules”. Among those, N-(3-oxododecanoyl)-l-homoserine lactone (AHL-12), generated by Pseudomonas aeruginosa and other Gram-negative bacteria, activates not only bacteria but also interacts with mammalian cells. Among others, it activates phagocytic cells and - as we had shown previously - it is chemotactic for human polymorphonuclear neutrophils (PMN) in vitro. In the present study, we analyzed the signalling pathway of AHL-12 in PMN. We focused on the mitogen activated protein (MAP) kinase p38, because SB203580, an inhibitor of p38, prevented the AHL-12 induced chemotaxis. We found that in response to AHL-12, p38 was phosphorylated within minutes, as was its downstream target, the MAPKAP-Kinase-2 (MK2). In PMN, the major substrate of MK2 is the leukocyte specific protein 1 (LSP1), which binds to F-actin and participates directly in actin polymerization and cell migration. In response to AHL-12, LSP1 was phosphorylated and co-localized with F-actin in polarized PMN, suggesting that AHL-12-induced migration depended on p38 and LSP1 activation.